2020
DOI: 10.3847/1538-4357/ababa0
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer by Nonlinear Alfvén Waves in the Solar Chromosphere and Its Effect on Spicule Dynamics, Coronal Heating, and Solar Wind Acceleration

Abstract: Alfvén waves are responsible for the transfer of magnetic energy in magnetized plasma. They are involved in heating the solar atmosphere and driving solar wind through various nonlinear processes. Because the magnetic field configurations directly affect the nonlinearity of Alfvén waves, it is important to investigate how they relate to the solar atmosphere and wind structure through the nonlinear propagation of Alfvén waves. In this study, we carried out one-dimensional magnetohydrodynamic simulations to real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…The energy transfer in the chromosphere can be attributed to a number of mechanisms, such as Alfven waves (Osterbrock 1961;Stein 1981;van Ballegooijen et al 2011;Shelyag et al 2016;Grant et al 2018;Sakaue & Shibata 2020), spicules (Beckers 1968;Pneuman & Kopp 1978;Athay & Holzer 1982;De Pontieu et al 2009;Beck et al 2016), nanoflares (Priest et al 2018;Syntelis & Priest 2020), and magneto-acoustic shocks (De Pontieu et al 2015). Some authors have suggested that the heating of the chromosphere is due to the dissipation of acoustic waves (Ulmschneider et al 1978;Kalkofen 2007), although this has been questioned by Athay & Holzer (1982) and Beck et al (2009Beck et al ( , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The energy transfer in the chromosphere can be attributed to a number of mechanisms, such as Alfven waves (Osterbrock 1961;Stein 1981;van Ballegooijen et al 2011;Shelyag et al 2016;Grant et al 2018;Sakaue & Shibata 2020), spicules (Beckers 1968;Pneuman & Kopp 1978;Athay & Holzer 1982;De Pontieu et al 2009;Beck et al 2016), nanoflares (Priest et al 2018;Syntelis & Priest 2020), and magneto-acoustic shocks (De Pontieu et al 2015). Some authors have suggested that the heating of the chromosphere is due to the dissipation of acoustic waves (Ulmschneider et al 1978;Kalkofen 2007), although this has been questioned by Athay & Holzer (1982) and Beck et al (2009Beck et al ( , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In this letter, therefore, we extend our recent solar atmosphere and wind model (Sakaue & Shibata 2020) to the M dwarf's atmosphere and wind. By carrying out the one-dimensional (1D) time-dependent MHD simulations, the nonlinear propagation of Alfvén wave in the nonsteady stellar atmosphere and wind is calculated from the M dwarf's photosphere, chromosphere, to the corona and interplanetary space.…”
mentioning
confidence: 91%
“…These difficulties in the above 3D global model have been addressed by the numerical studies about the nonlinear propagation of Alfvén wave along the single magnetic flux tube in the solar atmosphere from the photosphere, chromosphere, to the corona (Hollweg et al 1982;Kudoh & Shibata 1999;Matsumoto & Shibata 2010) and solar wind (Suzuki & Inutsuka 2005, 2006Matsumoto & Suzuki 2012Shoda et al 2018Shoda et al , 2019Sakaue & Shibata 2020;Matsumoto 2020). These approaches also have been extended to the stellar atmosphere and wind models (Suzuki et al 2013;Suzuki 2018;Shoda et al 2020), and revealed that the Alfvén wave amplitude on the top of chromosphere should be self-consistently determined as a consequence of wave dissipation and reflection in the chromosphere.…”
mentioning
confidence: 99%
“…The energy transfer in the chromosphere can be attributed to a number of mechanisms, such as Alfven waves (Osterbrock 1961;Stein 1981;van Ballegooijen et al 2011;Shelyag et al 2016;Grant et al 2018;Sakaue & Shibata 2020), spicules (Beckers 1968;Pneuman & Kopp 1978;Athay & Holzer 1982;De Pontieu et al 2009;Beck et al 2016), nanoflares (Priest et al 2018;Syntelis & Priest 2020), and magnetoacoustic shocks (De Pontieu et al 2015). Some authors have suggested that the heating of the chromosphere is due to the dissipation of acoustic waves (Ulmschneider et al 1978;Kalkofen 2007), although this has been questioned by Athay & Holzer (1982) and Beck et al (2009Beck et al ( , 2012.…”
Section: Introductionmentioning
confidence: 99%